Scarlet fever: a guide for general practitioners. Issue 5 (3rd September 2017) - Basetti, S.; Hodgson, J.; Rawson, T. M.; Majeed, A.
Abstract: There has been an increase in the incidence of scarlet fever with most cases presenting in General Practice and Emergency Departments. Cases present with a distinctive macro-papular rash, usually in children. This article aims to increase awareness of scarlet fever by highlighting key symptoms and stating potential complications if untreated. In patients who have the typical symptoms, a prescription of a suitable antibiotic such as phenoxymethylpenicillin (Penicillin V) should be made immediately to reduce the risk of complications and the spread of infection.